First satellite imaging of auroral pulsations by the Fast Auroral Imager on e‐POP. Issue 17 (3rd September 2015) - Lui, A. T. Y.; Cogger, L. L.; Howarth, A.; Yau, A. W.
Abstract We report the first satellite imaging of auroral pulsations by the Fast Auroral Imager (FAI) on board the Enhanced Polar Outflow Probe (e‐POP) satellite. The near‐infrared camera of FAI is capable of providing up to two auroral images per second, ideal for investigation of pulsating auroras. The auroral pulsations were observed within the auroral bulge formed during a substorm interval on 19 February 2014. This first satellite view of these pulsations from FAI reveals that (1) several pulsating auroral channels (PACs) occur within the auroral bulge, (2) periods of the intensity pulsations span over one decade within the auroral bulge, and (3) there is no apparent trend of longer pulsation periods associated with higher latitudes for these PACs. Although PACs resemble in some respect stable pulsating auroras reported previously, they have several important differences in characteristics.